K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

30 tháng 7 2021

x2 - y2 + a2 - b2 + 2ax + 2by

= ( x2 + 2ax + a2 ) - ( b2 - 2by + y2 )

= ( x + a )2 - ( b - y )2

= ( x + a - b + y ) ( x + a + b - y )

x3 - 2x2 - 6x + 27 

= ( x - 3 )3

30 tháng 7 2021

x3 35 2 = 688

30 tháng 7 2021

2)  x(x\(^2\)+2xy +y\(^2\)-9)= x((x+y)\(^2\)-9)= x(x+y-3) (x+y+3)

\(a)\)

\(4x^2-y^2+2x+y\)

\(=\left(4x^2-y^2\right)+\left(2x+y\right)\)

\(=\left(2x-y\right)\left(2x+y\right)+\left(2x+y\right)\)

\(=\left(2x+y\right)\left(2x-y+1\right)\)

\(b)\)

\(x^3+2x^2-6x-27\)

\(=x^3+5x^2+9x-3x^2-15x-27\)

\(=x\left(x^2+5x+9\right)-3\left(x^2+5x-9\right)\)

\(=\left(x-3\right)\left(x^2+5-9\right)\)

\(c)\)

\(12x^3+4x^2-27x-9\)

\(=\left(12x^3+4x^2\right)-\left(27x+9\right)\)

\(=4x^2\left(3x+1\right)-9\left(3x+1\right)\)

\(=\left(3x+1\right)\left(4x^2-9\right)\)

\(=\left(3x+1\right)[\left(2x\right)^2-3^2]\)

\(=\left(3x+1\right)\left(2x-3\right)\left(2x+3\right)\)

\(d)\)

\(16x^2+4x-y^2+y^2\)

\(=16x^2+4x\)

\(4x\left(4x+1\right)\)

25 tháng 10 2015

\(a,y-x^2y+2xy^2-y^3=y(1-x^2+2xy-y^2) =y[1-(x^2-2xy+y^2)]=y[1-(x-y)^2] =y(1-x+y)(1+x-y) =y(x+y-1)(x-y+1) \)

9 tháng 12 2018

a) \(2x\left(x-3\right)^2+5x\left(3-x\right)\)

\(=2x\left(x-3\right)^2-5x\left(x-3\right)\)

\(=\left(x-3\right)\left[2x\left(x-3\right)-5x\right]\)

\(=\left(x-3\right)\left(2x^2-6x-5x\right)\)

\(=\left(x-3\right)\left(2x^2-11x\right)\)

\(=x\left(x-3\right)\left(2x-11\right)\)

b) \(\left(x+3\right)^2-4\left(y^2-2y+1\right)\)

\(=\left(x+3\right)^2-2^2\left(y-1\right)^2\)

\(=\left(x+3\right)^2-\left[2\left(y-1\right)\right]^2\)

\(=\left[\left(x+3\right)-2\left(y-1\right)\right]\left[\left(x+3\right)+2\left(y-1\right)\right]\)

\(=\left(x+3-2y+2\right)\left(x+3+2y-2\right)\)

\(=\left(x-2y+5\right)\left(x+2y+1\right)\)

9 tháng 12 2018

a) \(2x.\left(x-3\right)^2+5x.\left(-x+3\right)=2x.\left(x-3\right)^2-5x.\left(x-3\right)\)

\(=\left(x-3\right).\left(2x^2-11x\right)=\left(x-3\right).x.\left(2x-11\right)\)

b) \(\left(x+3\right)^2-4.\left(y^2-2y+1\right)=\left(x+3\right)^2-2^2.\left(y-1\right)^2\)

 \(=\left(x+3\right)^2-\left[2.\left(y-1\right)\right]^2=\left(x-2y+1\right).\left(x+2y+5\right)\)

8 tháng 6 2017

a) \(=x^2+2xy+y^2-x^2+y^2=2xy+2y^2=2y\left(x+y\right)\)

b) \(=\left(x^2-4y^2\right)-\left(2x+4y\right)=\left(x-2y\right)\left(x+2y\right)-2\left(x+2y\right)=\left(x+2y\right)\left(x-2y-2\right)\)

c) \(=3\left[\left(x^2+2xy+y^2\right)-z^2\right]=3\left[\left(x+y\right)^2-z^2\right]=3\left(x+y+z\right)\left(x+y-z\right)\)

d) \(=\left(2xy+1+2x+y\right)\left(2xy+1-2x-y\right)\)

e) \(=\left(x-3\right)\left(x^2+3x+9\right)-2x\left(x-3\right)=\left(x-3\right)\left(x^2+x+9\right)\)

f) \(=\left(x+5\right)\left(x^2-5x+25\right)-x\left(x+5\right)=\left(x+5\right)\left(x^2-6x+25\right)\)

8 tháng 6 2017

a) \(\left(x+y\right)^2-\left(x^2-y^2\right)\)

\(=x^2+2xy+y^2-x^2+y^2\)

\(=2y^2+2xy\)

\(=2y\left(x+y\right)\)

c) \(3x^2+6xy+3y^2-3z^2\)

\(=3\left(x^2+2xy+y^2-x^2\right)\)

\(=3\left[\left(x+y\right)^2-z^2\right]\)

\(=3\left(x+y+z\right)\left(x+y-z\right)\)

d) \(\left(2xy+1\right)^2-\left(2x+y\right)^2\)

\(=\left(2xy+1+2x+y\right)\left(2xy+1-2x-y\right)\)

\(=\left[\left(2xy+2x\right)+\left(y+1\right)\right]\left[\left(2xy-2x\right)-\left(y-1\right)\right]\)

\(=\left[2x\left(y+1\right)+\left(y+1\right)\right]\left[2x\left(y-1\right)-\left(y-1\right)\right]\)

\(=\left(2x+1\right)\left(y+1\right)\left(2x-1\right)\left(y-1\right)\)

\(=\left(4x^2-1\right)\left(y^2-1\right)\)

27 tháng 9 2020

a,\(6x^3y^2-9x^2y^3+1^2x^2y^2\)

\(=x^2y^2\left(6x-9y+1\right)\)

b,\(2x\left(x-1\right)+3\left(1-x\right)\)

\(=2x\left(x-1\right)-3\left(x-1\right)\)

\(=\left(2x-3\right)\left(x-1\right)\)

27 tháng 9 2020

a,  

\(6x^3y^2-9x^2y^3+1\cdot x^2\cdot y^2\)

\(=x^2y^2\left(6x-9y+1\right)\) 

b,  

\(2x\left(x-1\right)+3\left(1-x\right)\) 

\(=2x\left(x-1\right)+3\cdot-1\left(x-1\right)\) 

\(=2x\left(x-1\right)-3\left(x-1\right)\) 

\(=\left(2x-3\right)\left(x-1\right)\)

8 tháng 8 2015

a)x4-1=(x2-1)(x2+1)=(x-1)(x+1)(x2+1)

b)x2-y2-2x+2y=(x-y)(x+y)-2(x-y)=(x-y)(x+y-2)

c)x2-6x-y2+9=(x2-6x+9)-y2=(x-3)2-y2=(x-y-3)(x+y-3)

d)5x2+3(x+y)2-5y2

=5(x2-y2)+3(x+y)2

=5(x-y)(x+y)+3(x+y)2

=(x+y)(5x-5y+3x+3y)

=(x+y)(8x-2y)

1 tháng 10 2016

a) 8x2 + 4xy - 2ax - ay = (8x2 + 4xy) - (2ax + ay) = 4x(2x + y) - a(2x + y) = (4x - a)(2x + y)

b) 2xy - x2 - y2 = 16 - (-2xy + x2 + y2) = 42 - (x - y)2 = (4 - x + y)(4 + x - y)

c) x2 - y2 - 2yz - z2 = x2 - (y2 + 2yz + z2) = z2 - (y + z)2 = (z - y - z)(z + y + z)

29 tháng 1 2020

a) \(6x^2-x-1\)

\(=6x^2-3x+2x-1\)

\(=3x\left(2x-1\right)+\left(2x-1\right)\)

\(=\left(3x+1\right)\left(2x-1\right)\)

29 tháng 1 2020

b) \(6x^2-6x-3\)

\(=3\left(2x^2-2x-1\right)\)